Development of NumeriUNO Media in Improving Mathematics Learning Outcomes of Grade III Students - Murtiana, Ananta Destian; Yulianto, Sigit (Jurnal Pendidikan Progresif, 2025)
Development of NumeriUNO Media in Improving Mathematics Learning Outcomes of Grade III Students. Objectives: This study aims to develop, and test the feasibility, effectiveness, and practicality of NumeriUNO card learning media to improve mathematics learning outcomes. Methods: The research model used is Research and Development (R&D) with the Borg & Gall development model. The research approach used in this study is a pre-experiment method with a one-group pretest-posttest design. Data collection techniques used to test techniques (pretest-posttest) and non-tests in the form of interview results, questionnaires, observations, score lists, and documentation. Findings: Media expert validation amounted to 92.3% and material experts amounted to 92.6% with very feasible criteria on both. The practicality test is shown by the results of students' responses 92% and by teachers 90%, with very positive categories in both. There is an increase in learning outcomes by 34.2 points, from the pretest results of 46.6 and posttest of 80.8. The effectiveness of the media is evidenced by a significant difference in the results of the two-sided t-test p (<0.001), the effect size value (Cohen's D) is 2.12, with a very large category of effects, n-gain of 0.6261 with a moderate category, and 77% of students experience learning completeness. Conclusion: The learning media of the NumeriUNO Card has proven to be not only feasible but also effective in improving students' mathematics learning outcomes on the multiplication of numbers. The use of games in learning increases student engagement, motivates them, and creates a more enjoyable and interactive learning experience. Keywords: NumeriUNO card, mathematic, learning outcomes.